(3Jbhje GdUMI HGdCSHGH GdSJIs - (3GdeNJGQ Hf GdMSf Hf YHOhf Hf HWdGf, GHf HWdGf,J (B444 (3g` s ((3OGhO Hf eZdWGj GdYajaj s)
(3ChdgG (B:s
(3Jbhje GdUMI HGdCSHGH GdSJI GdJj dGHO dcd EfSGf jDKQ OhGe UMJg ef JYOjdgG hGSJYeGdgG fHJOj HYhf Gdgd hfYed LOGhd JJYdjb HGdCZPjI hGdGTQHI hSGFQ eG JYOOg aj GdRGjQLI s
(3BNQgG (B:s
(3hdYd ef fbd cJGHj gPG jbhd EHOYJ h WhjdkG de GMJL Edi eG aj gPG GdcJGH ace eIQ LeYJ aj gPg GdGWYeI aj MGdI hGMOI hLQHJ Ydi GdCMhGd GdePchQI s
(3Vef eLehY , JQJjHgG (B: 1s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GgOGAGJ GdOcJhQ SRcjf (B(2069) s
Keywords: (3eJaQbGJs